Assessing the factors of training and development that effect staff performance at private hospital (Normah Medical Specialist Centre) Kuching, Sarawak. / Noor Syaffariza Ossen - Ossen, Noor Syaffariza (2019)
The major assets in the organization is the staff, they have a role to play towards a business success. Well trained and highly developed staffs are considered as comer stone for such success. Hence the purpose of the study was to assess the factors of training and development that effect staff performance in selected Private Hospital which are Normah Medical Specialist Centre located in the Northen region of Kuching. The questionnaire was formed based on the empirical literature. This research engaged simple random sampling technique for selecting the respondents. The independent variable that has been use in this research is policies and procedure, managerial support, validity of training and works environment. The dependent variable has been use in this research is staff performance. A quantitative research approach of the data collection was adopted using a Likert - Scale questionnaire including 35 questions was formed and the number of respondents is 266 staffs at Normah Medical Specialist Centre. The research employed descriptive analysis, correlation analysis and regression analysis. This data was collected by this research and was analysed by SPSS 20.0. The result shows that all independent variables have an insignificant impact on staff performance. Future researchers are recommended to add on other training and development factors.